Care experiences of older people with mental health needs and their families in emergency medical services settings. (26th August 2022) - Goode, Deborah; Ryan, Assumpta; Melby, Vidar; Slater, Paul
Abstract: Background: There are challenges to person‐centred care provision in Emergency Medical Services (EMS) settings. The environment is often busy and noisy which can influence the experience of older people and their carer/partners when they attend emergency departments. Older people with mental health needs are a vulnerable group of people who are at risk of not having their needs met in acute care settings. This is due to complex presentations and increased pressures on the EMS system. Aim: The aim of the paper was to explore the care experience of older people with mental health needs and their carer/partners in pre‐hospital and in‐hospital Emergency Medical Services settings. Method: This study used an interpretive qualitative approach incorporating in‐depth, individual interviews to gather information on the experience of the older person with mental health needs and carers/partners. Data were analysed using Braun and Clarke's (2006) thematic analysis. Results: Fifteen individual interviews were carried out with older people with mental health needs ( n  = 10) and with carers/partners ( n  = 5). Six themes on 'Getting there, getting in and getting out', 'Seeing the person', 'Perceptions and experiences of the pre‐hospital and Emergency Department (ED)', 'The effects of the experience on personal well‐being', 'Older person/carer/partner perceptions and experiences of the EMS staff' and 'Making it better' emerged from the data. Conclusions: The results suggest that previous experiences with the emergency care system influence the way older people with mental health needs and their carers make decisions on current and future care needs. Negative experiences can be influenced by the layout and organisation of the ED. Participants remain reluctant to discuss or disclose their diagnosis in the Emergency Medical Services setting due to a perceived stigma. Health and social care systems and services need to undergo transformations to ensure that all people who access services are treated fairly and effectively.